Biologic Interconversion of Hydrogen and Formate - Mourato, Cláudia Alhinho (2019)
"Hydrogen (H2) is one of the most promising energy vehicles in alternative to the use of fossil fuels. However, in order to use H2 as energy carrier it is necessary to find a safe, economically viable, and reasonably sized solution to store and transport it. Formate has emerged as an ideal storage compound for H2 as it is a safe compound, liquid at room temperature, which can be easily stored and transported, and furthermore it allows the sequestration of CO2 in a valuable commodity chemical. Nevertheless, for the implementation of a H2 and formate economy it is crucial to find efficient processes that can be used either for the use of formate as storage material for H2 production or for the conversion of H2 and CO2 to formate.(...)"